Twenty-Five Years After the ADA: Situating Disability in America’s System of Stratification - Maroto, Michelle; Pettinicchio, David (Disability Studies Quarterly, 2015)
Americans with disabilities represent a significant proportion of the population. Despite their numbers and the economic hardships they face, disability is often excluded from general sociological studies of stratification and inequality. To address some of these omissions, this paper focuses on employment and earnings inequality by disability status in the United States since the enactment of the 1990 Americans with Disabilities Act (ADA), a policy that affects many Americans. After using Current Population Survey data from 1988-2014 to describe these continuing disparities, we review research that incorporates multiple theories to explain continuing gaps in employment and earnings by disability status. In addition to theories pointing to the so-called failures of the ADA, explanations also include general criticisms of the capitalist system and economic downturns, dependence on social welfare and disability benefits, the nature of work, and employer attitudes. We conclude with a call for additional research on disability and discrimination that helps to better situate disability within the American stratification system.